LANGUAGE AND STYLE OF SIGNATURES - EMPIRICAL EXPERIENCE IN THE USE OF SPEECH GENRES (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Particular attention in the article is paid to the analysis of empirical experience in the use of speech genres and extralinguistic factors, which determines the interdisciplinary nature of the study. The relevance of the article is due to the growing role of the communicative-activity approach to language, the need to understand various types of discourse within the framework of communicative linguistics.